Integrasi Good Governance dan Digitalisasi dalam Optimalisasi Pengelolaan Wakaf Produktif: Pengembangan Model Pengelolaan Wakaf Berkelanjutan - Abd. Rahman; Sri Wahyuni Kasim; Kamaruddin Kamaruddin (Lembaga Yasin AlSys, 2026)
Productive waqf has great potential as an instrument for the economic empowerment and social development of the Muslim community, but the optimization of its management still faces challenges related to transparency, accountability, nazhir professionalism, and the use of digital technology. Although studies on waqf governance and digitalization have developed, research that integrates these two aspects into a sustainable productive waqf management model remains limited. This study aims to analyze the role of integrating good governance and digitalization in improving the effectiveness of productive waqf management and to formulate a sustainable waqf management model in the digital era. This study used a qualitative approach with a library research design. Data were obtained through a review of scholarly articles, books, institutional reports, and relevant documents discussing waqf governance, digital transformation, and productive waqf, then analyzed descriptively and interpretatively through reduction, categorization, and synthesis of findings. The results of the study show that transparency, accountability, participation, and professionalism are the main elements of good governance that can be strengthened through digitalization. The use of digital platforms, technology-based reporting systems, and digital waqf services can increase public trust, expand waqif participation, and support the effectiveness of waqf asset management. The success of waqf digitalization is also influenced by institutional capacity and nazhir competence. The conclusion of the study affirms that the integration of good governance and digitalization can form a more transparent, adaptive, accountable, and sustainable productive waqf management model. The implications of this study provide theoretical contributions to the development of modern waqf literature as well as practical recommendations for waqf institutions and policymakers in strengthening waqf governance in the digital era.